2022
DOI: 10.3390/app122111177
|View full text |Cite
|
Sign up to set email alerts
|

On the Privacy–Utility Trade-Off in Differentially Private Hierarchical Text Classification

Abstract: Hierarchical text classification consists of classifying text documents into a hierarchy of classes and sub-classes. Although Artificial Neural Networks have proved useful to perform this task, unfortunately, they can leak training data information to adversaries due to training data memorization. Using differential privacy during model training can mitigate leakage attacks against trained models, enabling the models to be shared safely at the cost of reduced model accuracy. This work investigates the privacy–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…In addition, the unintentional memorization [17] of training samples in these models could directly expose information about the training dataset. Surprisingly, while a plethora of research has been conducted on both document classification [5,6,35] and privacy in textual documents [13,14,18,30], we found no existing literature in the field that addresses the issue of data privacy and potential information leakage from AI-powered document image classification systems. In this work, therefore, we investigate the potential of latest privacy preservation techniques [22,23,26,28] in combination with state-of-the-art DL-based document image classification models to assess whether they can achieve sufficient utility under strong privacy constraints.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…In addition, the unintentional memorization [17] of training samples in these models could directly expose information about the training dataset. Surprisingly, while a plethora of research has been conducted on both document classification [5,6,35] and privacy in textual documents [13,14,18,30], we found no existing literature in the field that addresses the issue of data privacy and potential information leakage from AI-powered document image classification systems. In this work, therefore, we investigate the potential of latest privacy preservation techniques [22,23,26,28] in combination with state-of-the-art DL-based document image classification models to assess whether they can achieve sufficient utility under strong privacy constraints.…”
Section: Introductionmentioning
confidence: 83%
“…They further demonstrated that MIAs can be successfully applied to DL models, even with only a black-box access to the target model, achieved by training multiple shadow models that mimic the target model. A number of derivative works have further explored membership inference attacks in other tasks [10,13,14].…”
Section: Privacy Attacksmentioning
confidence: 99%
See 3 more Smart Citations